Assessment of consumers’ knowledge, attitude and perception of the impact of the COVID-19 pandemic on household food security in Caribbean Small Island Developing States - Daley, Oral; Roopnarine, Ronald; Isaac, Wendy-Ann P.; Palmer, Donald; John, Afiya; Webb, Marquitta; Dalrymple, Nequesha; Maharaj, Omardath (Frontiers in Sustainable Food Systems, 2023)
Introduction The COVID-19 pandemic and recent international crises including the Russia-Ukraine conflict have resulted in significant disruptions along multiple segments of the Caribbean’s agri-food system, thus compromising regional food security. These impacts are still ongoing with the potential to worsen. The aim of this study was to investigate the influence of sociodemographic factors on consumers’ knowledge of food security along with their attitude, and perception towards the impact of the COVID-19 pandemic on household food security in the Caribbean Small Island Developing States. Method A cross-sectional on-line survey was conducted between January 1 and November 30, 2021. The sampled population included consumers from nine Caribbean countries (Trinidad and Tobago, Barbados, Jamaica, Antigua and Barbuda, Dominica, Grenada, St. Kitts and Nevis, St. Lucia, and St. Vincent and the Grenadines). Survey data were analyzed using Chi-square, one way analysis of variance, and univariate logistic regression. Results and discussion A total of 237 consumers participated in the survey. Consumers were generally knowledgeable about food security and had favorable attitudes and perceptions of the impact of the COVID-19 pandemic on household food security. Significant associations (p<0.05) and significant differences (p<0.05) were obtained for consumers’ knowledge, attitude and perception among the sociodemographic variables assessed. The results suggest that there were different levels of vulnerability to food insecurity associated with the COVID-19 pandemic, particularly among economically vulnerable households. Policies that support disadvantaged households and ensure adequate employment opportunities are important to support Caribbean consumers throughout and post the COVID-19 pandemic recovery.